Adjuvant therapy in chromophobe renal cell carcinoma: current evidence and unmet needs - Niovi Bejjani; Joseph Kattan (Frontiers in Oncology, 2026)
Objectives Chromophobe renal cell carcinoma (chRCC) is a rare subtype of kidney cancer with biological and clinical features that differ significantly from clear cell renal cell carcinoma (ccRCC). While adjuvant treatments have evolved for ccRCC, chRCC has been excluded or understudied in clinical trials, which has led to insufficient histology-specific data to guide postoperative treatment. This research aimed to summarize and critically appraise the current evidence regarding adjuvant therapies for chRCC, highlight existing limitations in the literature, and identify priorities for future research. Methods A literature review was performed using PubMed and Google Scholar with search terms including “Carcinoma, Renal cell, Chromophobe, RCC, adjuvant, treatment, postoperative therapy, kidney cancer”. The search was limited to the last 10 years and included various study designs, ranging from phase III trials to case reports, that specifically addressed chRCC rather than grouping it broadly under non-clear cell RCC. Results Current clinical evidence does not support the routine use of adjuvant systemic therapies in chRCC. The phase III EVEREST trial failed to demonstrate a statistically significant improvement in recurrence-free survival for the mTOR inhibitor everolimus in the chRCC subgroup. Similarly, the ECOG ACRIN E2805 trial found that adjuvant VEGFR-targeted therapies, such as sunitinib and sorafenib, resulted in excessive toxicity without providing a disease-free survival benefit over placebo. Data on immune checkpoint inhibitors like pembrolizumab and nivolumab remain limited to metastatic settings with low objective response rates, resulting in insufficient evidence and a lack of expert consensus for their adjuvant use in chRCC. Conclusion There is a substantial lack of evidence supporting any reliable adjuvant therapy for chRCC, leaving high-risk patients without proven options after nephrectomy, and questioning the consistency of the extrapolation from metastatic clear-cell populations. However, given the rarity of chRCC and its comparatively low recurrence risk, a dedicated adjuvant randomized trial may be neither statistically nor logistically feasible; priorities should instead include first establishing an effective systemic therapy in the metastatic setting, pursuing pooled non–clear cell or registry-based collaborations, and developing biomarker-driven patient selection.